Patterns and influencing factors of exercise attendance of breast cancer patients during neoadjuvant chemotherapy - Goldschmidt, Siri; Schmidt, Martina; Rosenberger, Friederike; Wiskemann, Joachim; Steindorf, Karen (Supportive care in cancer, 2024)
Background: Performing 2–3 exercise sessions/week may relieve therapy-related side effects of breast cancer patients (BRCA) and improve their quality of life. However, attendance to the exercise sessions is often impaired. Thus, we investigated patterns and possible influencing factors of attendance to an aerobic (AT) or resistance training (RT) intervention in BRCA during neoadjuvant chemotherapy. Methods: BRCA (N = 122) were randomly allocated to supervised AT or RT twice weekly during neoadjuvant chemotherapy (18 ± 4 weeks). Attendance was calculated individually and group-wise per training week as the percentage of the performed sessions out of the prescribed sessions. Possible influencing factors were investigated using multiple regression analyses. Results: Mean individual attendance was 44.1% ± 29.3% with no significant differences between the groups. Group-wise attendance was highest in the first 6 weeks of training with ≥ 60% for AT and ≥ 50% for RT, but decreased over the course of the intervention accompanying chemotherapy. Significantly higher attendance was associated with not having vs. having nausea (ß =  − 14.57; p = 0.007) and not having vs. having pain (ß =  − 12.07; p = 0.12), whereas fatigue did not show any association (ß =  − 0.006; p = 0.96). Having been randomized into a preferred intervention group (48.8%) showed no association with attendance. Yet, patients’ rating of the exercise intervention as “good”/ “very good” (58.7%) was significantly associated with higher attendance (p = 0.01). Conclusion: For both exercise interventions, group-wise attendance/training week decreased during chemotherapy despite good intervention ratings. While some patients never started, others trained almost constantly twice weekly. The study revealed that patients who are nauseous or experience pain may need more support to attend more exercise sessions. Trial Registration Clinicaltrials.gov: NCT02999074 from May 6, 2016.
Gesehen am 27.03.2024